MAKNA SIMBOLIK “KEMBAR MAYANG” DALAM PERNIKAHAN ADAT JAWA DI KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Wati, Anggri Juwita; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Kembar mayang are one of the main requirements in the manten meeting procession in holding a traditional Javanese wedding, where kembar mayang themselves are neatly arranged flowers and leaves neatly and beautifully resembling a bouquet. In kembar mayang there are symbolic aspects that have certain meanings that are represented through the attributes used and human behavior in the use of kembar mayang. The purpose of this study is to determine the meaning of symbolic situations, the meaning of social interaction products, the meaning of interpretation on kembar mayang in traditional Javanese weddings in Bagan Sinembah District, Rokan Hilir Regency. This research uses descriptive qualitative method with interpretive paradigm. The informants in this study amounted to 10 people, namely, 2 traditional leaders, 2 kembar mayang makers, 2 masterminds of meeting manten, 2 parents of brides, and 2 brides by using purposive techniques. The results of this study show that the meaning of the symbolic situation of kembar mayang in Javanese traditional weddings in Bagan Sinembah District, Rokan Hilir Regency consists of physical objects and social objects, the meaning of social interaction products includes the meaning of each informant, the meaning of kembar mayang interpretations includes open actions and closed actions.